Study of the physical properties of selected active objects in the main belt and surrounding regions by broadband photometry. Issue 9 (30th November 2020) - Borysenko, Serhii; Baransky, Alexander; Kuehrt, Ekkehard; Hellmich, Stephan; Mottola, Stefano; Meech, Karen
Abstract: Dynamically different groups of comets and active asteroids with orbits at 2–5 a. u. show dust activity in varying degrees and forms. A photometric study and comparison of physical parameters can help to classify the mechanisms and nature of the activity for such objects. We present new observations using broadband photometry of 15 active objects in the main asteroid belt and surrounding regions obtained during 2012–2016. The study aims to compare the physical properties of main‐belt comets (MBCs), quasi‐Hilda comets (QHCs), and active asteroids (AAs). The observations were carried out with the 0.7‐m telescope of the Kyiv Comet Station, Ukraine, and with the 1.23‐m telescope at the Calar Alto Observatory, Spain, using Blue, Visual, Red (BVR) broadband filters. Upper limits for the nuclear radii, Afρ parameters, and color indices were measured. The results of 2012–2016 observations suggest that there exist systematic differences in the physical parameters of MBCs and QHCs.